Factors affecting the likelihood of the household to subscribe to Miag-ao Water District. - Majarucon, Carlyn Mae O.
The study identified the different factors affecting the likelihood of households to subscribe to Miag-ao Water District., There were 192 respondents from the four barangays in Miag-ao namely: Brgy. Bolho, Brgy. Sapa, Brgy. Tacas and Brgy. Ubos Ilaya. The dependent variable is the subscription decision of household, assuming a value of 1 if the respondent is willing to subscribe and 0 if not. The independent variables were classified into four: characteristics of the household head, characteristics of the household, geographical location and willingness to pay. The multivariate analysis revealed that all significant variables were found to affect the likelihood for subscription of 5% level. The chi-square value is 48.738, it shows that the whole model is significant in determining the likelihood of household to subscribe.